Mucinous breast cancer – clinical characteristics and treatment results in patients treated at the Oncology Centre in Kraków between 1952 and 2002 - Sas-Korczyńska, Beata; Mituś, Jerzy; Stelmach, Andrzej; Ryś, Janusz; Majczyk, Anna (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : To present the characteristics and clinical outcomes in 94 patients with mucinous breast cancer treated at the Oncology Centre in Krakow between 1952 and 2002. Material and methods: Stage I or II carcinomas were found in 66 patients (69.4%) of the presented group and in the remaining 28 patients (29.8%) stage III disease was diagnosed. In 27 cases regional lymph nodes were involved. All patients had been treated with surgery: mastectomy (90 patients) or breast-conserving treatment (4 patients). Radiotherapy was administered in 14 patients, adjuvant chemo- therapy in 14 patients, and endocrine therapy in 39 patients. Results : The maximum follow-up was 257 months. Ten-year survival was as follows: 75.7% (overall survival), 82.5% (disease-free survival). During the follow-up, 4 patients developed local recurrence, 5 patients developed metastases. Second primary cancer was found in 8 patients. Conclusions : The presented results confirm the good prognosis in patients treated for mucinous breast cancer. The diagnosis of early-stage breast cancer based on mammography can allow breast-conserving treatment.